NILAI WAKTU DARI UANG DALAM PERSPEKTIF EKONOMI ISLAM - Fatrilia Rasyi Radita (Journal Of Communication Education, 2019)
Abstract: The time value of money is associated with the current value andfuture value because the money received now is more worth than the money received in the future. However, is the concept of time value of money is appropriate and justified by the Shari'ah? The time value of money is a concept that says that the money of the one rupiah that can be received today is more worth than one rupiah which will be received in the future time. The concept of time value of money is needed by financial managers in making decision when will invest in an asset and determine the source of loan funds that will be chosen. Methods for the time value of money pervade; a) the method of average rate of return. This method measures the level of profit gained by an investment. The disadvantage of this method is ignoring the time value of money; b) the payback period method. The method measures how fast the investment return is, the sooner the better; c) method of net present value (NPV). This method calculates quarrel between the current value of investment and the present value of net cash receipts in the future and calculates quarrel between the present value of cash outflow (investment) and cash inflow (income) per year; d) profitability index method (PI). This method calculates ratio between the present value of net cash receipts in the future and the present value of the investment; and e) the methods of internal rate of return (IRR). If IRR > saving or profit required→ decent. Islamviews money as a flow concept. Money must rotate in an economy and may not be idle for too long time. Moreover, it lets for years. Islam does not recognize the method of time value of money because this method adds value to money solely with increasing time and not effort. Islam actually knows the money value of time; that is the time has economic value as well as the money value of money. Imam Nawawi provides definition related to value addition for money based solely on the value of time is the category of riba. Keywords: time value of money, Islamic economics